Penggunaan media literacy cloud untuk meningkatkan kemampuan membaca pemahaman peserta didik kelas VA di sekolah dasar - Oka Titin Pratiwi; Retno Winarni (Didaktika Dwija Indria, 2025)
This study aims to explain the use of Literacy Cloud media to improve the reading comprehension skills of fifth-grade students at SDN Dukuhan Kerten Surakarta. This study uses classroom action research (CAR) based on the Kemmis and Mc Taggart model with the following stages: (1) planning, (2) implementation of actions, (3) observation, (4) reflection. This classroom action research was conducted by the teacher in two cycles, each consisting of two meetings, to address learning issues in the classroom. The research subjects were 24 students in class VA. Data collection techniques in this study included interviews, observations, and tests. The research data were analyzed qualitatively and quantitatively descriptively. The results of this study indicate an increase in reading comprehension skills among students after using the Literacy Cloud media. The results obtained were seen from the percentage of student achievement, which increased from 45.83% to 79.16%. The challenges identified include some students who tend to work independently during lessons, students who lack confidence, and students who are less engaged in group discussions. The solutions implemented include teachers advising students, providing motivation, and assigning each student a specific role in group discussions